Avaliação microbiológica da superfície implantar: estudo clínico comparando implantes submersos, não submersos e carga imediata - Furquim, Fábio (2018)
A few studies have been conducted on dental implants in order to investigate the microbial contamination around the implants and in the microgap existing between implant/abutment. The aim of the present study was to evaluate the microbial contamination on the internal and external parts of the implant walls in cone morse implants. Eleven patients of both sexes and with edentulous sites in the mandibular posterior area were selected. All patients received three dental implants. The implants were divided into three groups: Submerged (S), Non-Submerged (NS) and Immediately Loaded (IL), according to the installation protocol. The S group implants received a delayed loading and remained submerged until the reopening phase and subsequent prosthetic rehabilitation. The NS group implants received a delayed loading (healing screws were installed) until the prosthetic rehabilitation phase. The IL group implants received immediate loading without abutment removal for prosthetic rehabilitation. The microbiological evaluations were divided into internal collection and external collection of the implant walls, at different stages, T0 (surgical procedure), T2 (Suture Removal), T4 (Reopening group S), T6 (Suture removal group S), T8 (Abutment placement in groups S and NS). The microbiological variables analyzed were the number of microorganisms measured by spectrophotometry at the time of collection and 24 hours after cultivation, the number of aerobic and anaerobic colony forming units (CFU), and qualification of types of microorganisms. All obtained data was submitted to a descriptive and statistical analysis of the results, with a 0.05 significance level, using SPSS 24.0 software. The spectrophotometric evaluation demonstrated a significant difference with respect to the number of microorganisms observed over time within the same group, either by internal or external collections (p<0.05). Regarding the evaluation of the number of microorganisms compared between groups, no difference was observed (p>0.05). With respect to the number of CFU, statistically significant difference was observed, on both aerobic and anaerobic cultures, when evaluated within the same group over time (p<0.05), except for the IL group. However, there was no statistically significant difference when the groups were compared at the same stage (p> 0.05). Regarding the gram staining, in the internal collection of the implant wall, it was observed a predominance of nonformation of microorganisms at T0 in all groups, with formation of Gram-positive Diplococci and Gram-positive Bacilli at T8. On the other hand, in the external collection, an increase in the number of microorganisms was observed at T0, when compared to the internal collection. Fungi were also predominant in the external collection. Finally, it is possible to infer that there is no difference in the microbial contamination between the evaluated groups, with significant differences only with respect to the microrganisms colonization over time.